Analyzing the Role of Emotional Intelligence and Transformational Leadership During the CoV-19 Pandemic - Ardi; Sally Notariza Taher; Margaretha Pink Berlianto; Kezia Arya Nanda (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Recent decades have seen a movement in successful leadership theorizing, views, and study toward an emphasis on interpersonal skills and the leader's ability to inspire, encourage, and motivate subordinates and generate and sustain a good feeling of participation to the whole organization. Previous research and conceptions of leadership have tended to center on command and control, strategic planning, and goal setting, but this new approach takes a very different tack. Therefore, the basis of this essay is the connection between emotional intelligence (leading from the heart) and transformational leadership in the context of COVID-19 (coronavirus) pandemic difficulties. It is therefore argued here that a leadership style that centers on emotional intelligence mediated by transformational leadership can be instrumental in guiding business organizations through the times of crisis that humanity (and the organization specifically) is currently facing, unleashed by the COVID-19 pandemic challenges. The method utilized in this essay is based on a fast review of the current literature on these occurrences and how it may be used to develop a conceptual framework that could provide novel insights into how to effectively address the difficulties of Covid-19 with strong leadership. The conclusion of this essay is that in times of crisis – such as the one that was brought about by Covid-19 – a combination of emotional intelligence and transformational leadership is required to create meaningful change within an organization. This will allow the organization to recover and continue to function economically and sustainably.